AIAA Aerodynamic Decelerator Systems (ADS) Conference 2013
DOI: 10.2514/6.2013-1289
|View full text |Cite
|
Sign up to set email alerts
|

An Airborne Parachute Compartment Test Bed for the Orion Parachute Test Program

Abstract: The test program developing parachutes for the Orion/MPCV includes drop tests with parachutes deployed from an Orion-like parachute compartment at a wide range of dynamic pressures. Aircraft and altitude constraints precluded the use of an Orion boilerplate capsule for several test points. Therefore, a dart-shaped test vehicle with a hi-fidelity mockup of the Orion parachute compartment has been developed. The available aircraft options imposed constraints on the test vehicle development and concept of operati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…The missile-shaped Parachute Compartment Drop Test Vehicle (PCDTV) allowed for stable high-speed deployments with representative suspension hardware and could be extracted from either a C-130 or C-17. 4 The Parachute Test Vehicle (PTV) provided an Orion "boilerplate" which was somewhat truncated in height in order to fit in a C-17. 5 The latter two vehicles are currently in use for the qualification portion of the test program.…”
Section: Introductionmentioning
confidence: 99%
“…The missile-shaped Parachute Compartment Drop Test Vehicle (PCDTV) allowed for stable high-speed deployments with representative suspension hardware and could be extracted from either a C-130 or C-17. 4 The Parachute Test Vehicle (PTV) provided an Orion "boilerplate" which was somewhat truncated in height in order to fit in a C-17. 5 The latter two vehicles are currently in use for the qualification portion of the test program.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive Monte Carlo analysis was performed on the PCDTV tests to balance the risk of releasing too late (or not at all) with the risk of a sub-optimal release point because the back-up timer was set too early. 6 A similar analysis was undertaken for the first PTV test but it indicated that the results were highly dependent on the failure mode and that there were few suboptimal (time-based) releases that would not result in a tumbling PTV. Back-up release times that would help in one failure mode would make things worse in other failure modes.…”
Section: Time Window Analysismentioning
confidence: 98%
“…The CPAS project developed and refined this technique over several drop tests 5 including the PCDTV tests that preceded the PTV series of tests. 6 …”
Section: Smart Separationmentioning
confidence: 99%
“…However, design of a parachute system for the Orion capsule still utilizes the linear aerodynamic theory available in NASTRAN while modeling the multi-body dynamics using the ADAMS module [4].…”
Section: Introductionmentioning
confidence: 99%